Is spatial planning a collaborative learning process? A case study from a rural–urban gradient in Sweden. (November 2015) - Elbakidze, Marine; Dawson, Lucas; Andersson, Kjell; Axelsson, Robert; Angelstam, Per; Stjernquist, Ingrid; Teitelbaum, Sara; Schlyter, Peter; Thellbro, Camilla
Highlights: Strategic spatial planning should be a process of collaborative learning amongst involved stakeholders. The paper presents key normative attributes of strategic spatial planning as a collaborative learning process. Utilises both qualitative and system thinking methods to analyse strategic spatial planning in Central Sweden. Many of the normative attributes of strategic spatial planning needed for collaborative learning have been absent or undeveloped in the studied municipalities. Stakeholder participation is the key determinant of the scale and depth of planning processes. To encourage collaborative learning there is a need for arenas allowing and promoting stakeholder activity, participation and inclusion that represents all societal sectors at multiple levels. There is a need for improved methods for synthesising different stakeholder views as well as evidence-based knowledge. Abstract: International and national policies stress the importance of spatial planning for the long-term sustainability of regions. This paper identifies the extent to which the spatial planning in a Swedish region can be characterised as a collaborative learning process. By combining qualitative interviews and systems thinking methods we analysed the main attributes of public-led spatial (i.e. comprehensive) planning in nine municipalities representing a steep urban–rural gradient in the Bergslagen region of Central Sweden. We show that the attributes of strategic spatial planning needed for collaborative learning were absent or undeveloped. All studied municipalities experienced challenges in coordinating complex issues regarding long-term planning to steer territorial development and help to solve conflicts among competing interests. Stakeholder participation was identified as a basic condition for social learning in planning. Together with stakeholders we identified the causal structure behind stakeholder participation in municipal planning processes, including main drivers and feedback loops. We conclude that there is a need for arenas allowing and promoting stakeholder activity, participation and inclusion that combines both bottom-up and top-down approaches, and where evidence-based collaborative learning can occur.